Mutations in KAT6B, Encoding a Histone Acetyltransferase, Cause Genitopatellar Syndrome - Campeau, Philippe M.; Kim, Jaeseung C.; Lu, James T.; Schwartzentruber, Jeremy A.; Abdul-Rahman, Omar A.; Schlaubitz, Silke; Murdock, David M.; Jiang, Ming-Ming; Lammer, Edward J.; Enns, Gregory M.; Rhead, William J.; Rowland, Jon; et al. (American journal of human genetics, 2012)
Genitopatellar syndrome (GPS) is a skeletal dysplasia with cerebral and genital anomalies for which the molecular basis has not yet been determined. By exome sequencing, we found de novo heterozygous truncating mutations in KAT6B (lysine acetyltransferase 6B, formerly known as MYST4 and MORF) in three subjects; then by Sanger sequencing of KAT6B, we found similar mutations in three additional subjects. The mutant transcripts do not undergo nonsense-mediated decay in cells from subjects with GPS. In addition, human pathological analyses and mouse expression studies point to systemic roles of KAT6B in controlling organismal growth and development. Myst4 (the mouse orthologous gene) is expressed in mouse tissues corresponding to those affected by GPS. Phenotypic differences and similarities between GPS, the Say-Barber-Biesecker variant of Ohdo syndrome (caused by different mutations of KAT6B), and Rubinstein-Taybi syndrome (caused by mutations in other histone acetyltransferases) are discussed. Together, the data support an epigenetic dysregulation of the limb, brain, and genital developmental programs.